2011
DOI: 10.1002/pbc.23139
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for smoking among adolescent survivors of childhood cancer: A report from the childhood cancer survivor study

Abstract: Background Few studies have examined risk factors for smoking among adolescent survivors of childhood cancer. The present study reports on the rate of smoking and identifies factors associated with smoking in a sample of adolescent survivors from the Childhood Cancer Survivor Study (CCSS). Procedure Participants included 307 adolescent survivors and 97 healthy siblings (ages 14-20) who completed a self-report survey of health, quality of life, and health behaviors. Results Smoking rates did not differ sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 50 publications
3
43
1
4
Order By: Relevance
“…Kahalley et al [32] also found no significant difference in smoking rates between childhood cancer survivors and healthy sibling controls. However, Kahalley et al did address the correlation between the increased incidence of smoking and health risk factors, such as peer smoking, household smoking and suicidal behavior.…”
Section: Cardiotoxicity Risk Factorsmentioning
confidence: 96%
“…Kahalley et al [32] also found no significant difference in smoking rates between childhood cancer survivors and healthy sibling controls. However, Kahalley et al did address the correlation between the increased incidence of smoking and health risk factors, such as peer smoking, household smoking and suicidal behavior.…”
Section: Cardiotoxicity Risk Factorsmentioning
confidence: 96%
“…Due to improved therapy, 80 % of the children diagnosed with cancer will become long-term survivors [33]. Long-term survivors of childhood cancers are at increased risk of late mortality compared with the general population mainly due to treatment-related secondary neoplasms, and cardiac, and pulmonary deaths [31,[34][35][36][37]. A Nordic study by Moller et al [6] reported a reduction in the overall late mortality among long-term childhood cancer survivors over time.…”
Section: Comparison With the Literaturementioning
confidence: 97%
“…Quatre s'intéressent aux différents comportements à risque dont l'alcool et le cannabis chez les adolescents et jeunes adultes ayant eu un cancer [5][6][7][8]. Trois articles concernent exclusivement le tabagisme [9][10][11] ; 6 articles concernent l'alimentation et l'activité physique [12][13][14][15][16][17]. Un article concerne exclusivement l'exposition solaire chez les enfants, adolescents et jeunes adultes ayant eu un cancer [18].…”
Section: Facteurs Comportementauxunclassified
“…Parmi les cinq études qui abordent la question du tabagisme chez les jeunes ayant eu un cancer [6,7,[9][10][11], trois d'entre elles sont exclusivement dédiées au tabagisme [9][10][11]. Le tabagisme varie de 10 à 29 % dans cette population, selon les études.…”
Section: Tabacunclassified
See 1 more Smart Citation